Maternal blood metal and metalloid concentrations in association with birth outcomes in Northern Puerto Rico. (May 2020) - Ashrap, Pahriya; Watkins, Deborah J.; Mukherjee, Bhramar; Boss, Jonathan; Richards, Michael J.; Rosario, Zaira; Vélez-Vega, Carmen M.; Alshawabkeh, Akram; Cordero, José F.; Meeker, John D.
Highlights: First study to assess maternal metals in relation to birth outcomes in Puerto Rico. Highlights the importance of assessing the effects of mixtures on health outcomes. Pb, even at low-levels, was the most strongly associated with risk of preterm birth. Elevated Mn and Zn exposure may adversely affect birth outcomes. Abstract: Background: In previous studies, exposures to heavy metals such as Pb and Cd have been associated with adverse birth outcomes; however, knowledge on effects at low levels of exposure and of other elements remain limited. Method: We examined individual and mixture effects of metals and metalloids on birth outcomes among 812 pregnant women in the Puerto Rico Testsite for Exploring Contamination Threats (PROTECT) cohort. We measured 16 essential and non-essential metal(loid)s in maternal blood collected at 16–20 and 24–28 weeks gestation. We used linear and logistic regression to independently examine associations between geometric mean (GM) concentrations of each metal across visits and gestational age, birthweight z-scores, preterm birth, small for gestational age (SGA), and large for gestational age (LGA). We evaluated effect modification with infant sex*metal interaction terms. To identify critical windows of susceptibility, birth outcomes were regressed on visit-specific metal concentrations. Furthermore, average metal concentrations were divided into tertiles to examine the potential for non-linear relationships. We used elastic net (ENET) regularization to construct Environmental Risk Score (ERS) as a metal risk score and Bayesian Kernel Machine Regression (BKMR) to identify individual metals most critical to each outcome, accounting for correlated exposures. Results: In adjusted models, an interquartile range (IQR) increase in GM lead (Pb) was associated with 1.63 higher odds of preterm birth (95%CI = 1.17, 2.28) and 2 days shorter gestational age (95% CI = −3.1, −0.5). Manganese (Mn) and zinc (Zn) were also associated with higher odds of preterm birth and shorter gestational age; the associations were strongest among the highest tertile for Mn and among females for Zn. Mercury (Hg) was associated with higher risk of preterm birth at the later window of pregnancy. Ni measured later in pregnancy was associated with lower odds of SGA. ENET and BKMR models selected similar metals as "important" predictors of birth outcomes. The association between ERS and preterm birth was assessed and the third tertile of ERS was significantly associated with an elevated odds ratio of 2.13 (95% CI = 1.12, 5.49) for preterm birth compared to the first tertile. Conclusion: As the PROTECT cohort has lower Pb concentrations (GM = 0.33 μg/dL) compared to the mainland US, our findings suggest that low-level prenatal lead exposure, as well as elevated Mn and Zn exposure, may adversely affect birth outcomes. Improved understanding on environmental factors contributing to preterm birth, together with sustainable technologies to remove contamination, will have a direct impact in Puerto Rico and elsewhere.